2010
DOI: 10.1164/rccm.201003-0334oc
|View full text |Cite
|
Sign up to set email alerts
|

Specific T Cell Frequency and Cytokine Expression Profile Do Not Correlate with Protection against Tuberculosis after Bacillus Calmette-Guérin Vaccination of Newborns

Abstract: Rationale: Immunogenicity of new tuberculosis (TB) vaccines is commonly assessed by measuring the frequency and cytokine expression profile of T cells. Objectives: We tested whether this outcome correlates with protection against childhood TB disease after newborn vaccination with bacillus Calmette-Guérin (BCG). Methods: Whole blood from 10-week-old infants, routinely vaccinated with BCG at birth, was incubated with BCG for 12 hours, followed by cryopreservation for intracellular cytokine analysis. Infants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
315
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 381 publications
(333 citation statements)
references
References 48 publications
12
315
3
3
Order By: Relevance
“…Concerning the qualitative differences in immune responses observed between TB disease and LTBI, conflicting findings were previously reported, particularly on the role of IFN-γ + TNF-α + IL-2 + triple positive T cells, which has been proposed as a hallmark of TB disease [30][31][32], as well as of LTBI [33][34][35]. In addition, recent vaccine trials have revealed that these multifunctional triple positive cells not necessarily offer protection in humans [36,37]. Although a number of differences in the experimental setup can be identified between these studies, none of them can directly explain these conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the qualitative differences in immune responses observed between TB disease and LTBI, conflicting findings were previously reported, particularly on the role of IFN-γ + TNF-α + IL-2 + triple positive T cells, which has been proposed as a hallmark of TB disease [30][31][32], as well as of LTBI [33][34][35]. In addition, recent vaccine trials have revealed that these multifunctional triple positive cells not necessarily offer protection in humans [36,37]. Although a number of differences in the experimental setup can be identified between these studies, none of them can directly explain these conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both animal models and human clinical trials have shown that the IFN-g response to BCG vaccination is not predictive of subsequent protection from TB (Elias et al 2005;Mittrucker et al 2007;Kagina et al 2010), and recent data suggest that instead of boosting "more of the same" Th1 response it may be better to promote responses that are insufficiently promoted by BCG and mediated by T cells devoid of or low in IFN-g expression (Goldsack and Kirman 2007;Lindenstrom et al 2013). …”
Section: Novel Vaccination Strategies Against Tbmentioning
confidence: 99%
“…Although vaccine immunogenicity is currently measured based on the prototypic TH1 cell cytokine (IFN ) responses from cells in peripheral blood, recent data raise concern that these parameters may not correlate with risk of disease (Kagina et al, 2010). Th1 specific cytokine responses, including of polyfunctional T cells, measured at 10 weeks post-immunization did not correlate with risk of disease in BCG vaccinated newborns followed for two years.…”
Section: Biomarkersmentioning
confidence: 99%